Design of the Feeding and Blanking Manipulator for Punch and Driving System - Guo Bin; Wang Yanming; Lu Yi; Zhao Jing (Jixie chuandong)
A kind of joint type feeding and blanking manipulator for punch is designed,which regards sheet parts as the material and takes motion control card as the core of control. Each joint is driven by servo motors to make the load to lifting,rotate,move and swing. Then,the load transfer of the manipulator is analyzed based on manipulator movement and transformation principles of torque and inertia,the selection of the servo is completed.Also,the verification of the selection is carried out with the theory. Based on the completion of hardware configuration,the working process of manipulator is determined in view of its actual working condition.